RESEARCH ON CLUSTERING CONDITIONS IN SOUTH AFRICA - Diana-Cosmina CHIFOR; Felix ARION (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Initially, clusters focused on creating a framework for cooperation between economic actors, research institutes, and public authorities from the same geographical concentration. Considering the European cluster model as a way of developing solid cooperation, the same steps were presented to find the interest of South African’s economic actors in developing a feasible partnership model. This includes analyses on a wider scale, such as the degree of development of the compared countries where the model was implemented, the particularities and political priorities, the fields of activity. Going forward, the next steps that can be done are: mapping the existing clusters and their operating characteristics, assessing the regional business environments and the degree of competitiveness. After carrying out the analysis, there is concern about whether this concept can be implemented in countries like South Africa. Additional investigation will focus on other elements that affect the model's successful application.